THE DIFFERENT AIR TEMPERATURE IN THE SHADOWED AND UNSHADOWED CONDITION Case Study: Ci-Walk, Old Town, Semarang. - Akbar Rahman (JURNAL PERSPEKTIF ARSITEKTUR, 2011)
An experimental study has been the simulation of shadowing pattern of buildings line attributed to thecomfort of pedestrian ways with the case study on ci-walk, old town Semarang. Since the pavementbeen made, there were only few pedestrian make use of it. These circumstances rises an indicationthat this pedestrian ways was not comfortable enough for the pedestrian due directly into sun radiation.It was believed that any barrier causing the sun radiation to indirectly hit the body would give somecomfort for the pedestrian. This direct sun’s radiation barrier would cause some shadow patterns,where on the open space this pattern could be produced from surrounding buildings line. The resultwas, The unshadowed and shadowed air temperature give significant differences to the effective temperaturevalue achieved. The most uncomfortable effective temperature was one that not shadowed bythe building on ci-walk pedestrian ways, old town on Semarang.